2018
DOI: 10.3390/vision2020017
|View full text |Cite
|
Sign up to set email alerts
|

Differential Angular Expansion in Perceived Direction in Azimuth and Elevation Are Yoked to the Presence of a Perceived Ground Plane

Abstract: It has been proposed that perceived angular direction relative to straight-ahead is exaggerated in perception, and that this exaggeration is greater in elevation (or declination) than in azimuth. Prior research has suggested that exaggerations in elevation may be tied to the presence of a visual ground plane, but there have been mixed results across studies using different methods of dissociation. In the present study, virtual environments were used to dissociate visual from gravitational upright while human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The current investigation was inspired by a prior work examining the role of the perceived ground plane on the explicit estimation of the perception of the azimuth. Using a large stereoscopic virtual display, it was found that, for a seated observer, estimates of the visual direction to a depicted ball off to one side (relative to a distant reference post straight ahead) were expanded with a gain of 1.25 when the scene depicted a ground plane, but they were only exaggerated with a gain of about 1.05 when a world was not depicted, other than the central vertical line extending from the bottom to the top of the screen [ 60 ]. In other words, the perceptual expansion of the angular direction in azimuth seemed to be triggered by the ground plane being visible.…”
Section: Introductionmentioning
confidence: 99%
“…The current investigation was inspired by a prior work examining the role of the perceived ground plane on the explicit estimation of the perception of the azimuth. Using a large stereoscopic virtual display, it was found that, for a seated observer, estimates of the visual direction to a depicted ball off to one side (relative to a distant reference post straight ahead) were expanded with a gain of 1.25 when the scene depicted a ground plane, but they were only exaggerated with a gain of about 1.05 when a world was not depicted, other than the central vertical line extending from the bottom to the top of the screen [ 60 ]. In other words, the perceptual expansion of the angular direction in azimuth seemed to be triggered by the ground plane being visible.…”
Section: Introductionmentioning
confidence: 99%